(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The Maiden of Yue story is a short, legendary tale that describes the essence of Chinese martial arts theory. It is the earliest such description in Chinese history (written 25-220 C.E.) and has been quoted or paraphrased by other martial artists over the centuries, including Wu Yuxiang (1812-1880) (Xu, 1936: Part 3, 52), the first individual to compile and transmit what came to be known as Taijiquan theory. The story concisely describes both internal and external characteristics that combine mental and physical attributes and counter the fallacy of later artificial categorizations of the Chinese martial arts into Internal and External Schools.